Selection of nitrification and denitrification bacteria with its application in culture medium of Pacific white shrimp (Litopenaeus vannamei) - Widanarni, .; Pranoto, Sugiyo Hadi; Sukenda, . (Indonesian Society of Scientific Aquaculture (ISSA), 2010)
The aim of this study was to obtain nitrification and denitrification bacteria and tested its activity in reducing the ammonia, nitrite and nitrate compounds in culture medium of Pacific white shrimp Litopenaeusvannamei. The research was conducted through several steps: 1) Isolation of nitrification and denitrification bacteria from ponds and mangrove areas, 2) Selection of nitrification and denitrification bacteria in vitro, and 3) test of the nitrication and denitrification bacteria activities in culture medium of white shrimp. A total of 38 isolates of nitrification bacteria and 7 isolates of denitrification bacteria were successfully isolated from ponds and mangrove areas in the region of South Lampung and Subang, West Java. Of the total isolates were then selected in vitro based on its ability to reduce the compounds of ammonia, nitrite and nitrate and selected each 2 of the best isolates. Two select nitrification bacteria isolates, namely S11 and S12 each can oxidize ammonia at 78.25% and 80.54%, whereas two select denitrification bacteria isolates namely DS7 and DS3 each can reduce nitrate amounted to 85.41%, and 56, 49%. The test results of nitrification and denitrification bacteria activities in culture medium of white shrimp showed that S12-DS7 treatments gave the best result, with ammonia concentrations between 0.007 - 0.13 mg / l, nitrite of 0.04 -2.34 mg / l, nitrate of 1 0.33 - 3, 29 mg / l, shrimp growth rate of 2.1%, and survival rate of 90%.Keywords: nitrification, denitrification, Litopenaeus vannamei, water quality. ABSTRAKPenelitian ini bertujuan untuk mendapatkandan menguji aktivitasbakteri nitrifikasi dan denitrifikasi dalam mengurangi senyawa amonia, nitrit dan nitrat pada media budidaya udang vaname Litopenaeus vannamei. Penelitian dilakukan melalui beberapa tahap yaitu: 1) Isolasi bakteri nitrifikasi dan denitrifikasi dari lingkungan tambak dan mangrove, 2) Seleksi bakteri nitrifikasi dan denitrifikasi secara in vitro, dan 3) Uji aktivitas bakteri nitrifikasi dan denitrifikasi pada media budidaya udang vaname.Sebanyak 38 isolat bakteri nitrifikasi dan 7 isolat bakteri denitrifikasi berhasil diisolasi dari lingkungan tambak dan mangrove di daerah Lampung Selatan dan Subang, Jawa Barat. Dari total isolat tersebut kemudian diseleksi secara in vitro berdasarkan kemampuannya dalam menurunkan senyawa amonia, nitrit dan nitrat dan dipilih masing-masing 2 isolat terbaik. Dua isolat bakteri nitrifikasi terseleksi yaitu S11 dan S12 masing-masing dapat mengoksidasi amonia sebesar 78,25% dan 80,54%, sedangkan dua isolat bakteri denitrifikasi terseleksi yaitu DS3 dan DS7 masing-masing dapat mereduksi nitrat sebesar 85,41% dan 56,49%. Hasil uji aktivitas bakteri nitrifikasi dan denitrifikasipada media budidaya udang vaname menunjukkan bahwa perlakuan S12-DS7 memberikan hasil terbaik, dengan konsentrasi amonia berkisar antara 0,007-0,13 mg/l, nitrit 0,04-2,34 mg/l, nitrat 1,33-3,29mg/l,laju pertumbuhan udang sebesar 2,1%, dan kelangsungan hidup 90%.Kata kunci: nitrifikasi, denitrifikasi, Litopenaeus vannamei, kualitas air